2021
DOI: 10.3390/antiox10101521
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Characterization of Phenolic Compounds from Australian Grown Bananas and Their Antioxidant Capacity

Abstract: Bananas are an essential source of staple food and fruit worldwide and are widely regarded as the world’s largest fruit crop, with more than 100 million tons total annual production. Banana peel, a by-product that represents about 40% of the entire banana’s weight, and pulp are rich in bioactive compounds and have a high antioxidant capacity. As the production of polyphenols in fruit and vegetables is highly dependent on environmental conditions, genetic factors, and the level of maturity, this study aims to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 68 publications
5
47
0
Order By: Relevance
“…The above results verified that the type and content of phenolic compounds in banana peel were varied depending on the variety of banana [11,16]. Similarly, research by Bashmil et al, showed that the highest phenolic compound contents were found in the ripe Ducasse peel, unripe Ladyfinger peel, ripe Plantain peel, and unripe Monkey peel, which contained 1.32, 1.15, 0.87, and 0.79 mg GAE/g, respectively [38]. Baskar et al [39] also found that among the nine local cultivars from Tamil Nadu, India, Poovan cultivar had less total phenolic compound content (0.39 mg catechol equivalent (CE)/g), but higher level of flavonoids (22.83 mg rutin equivalent (RE)/g) in comparison with other cultivars, such as Sevvazhai, Nendran, and Rasthali.…”
Section: Quantitative Analysis Of Main Phenolic Compounds In Ripe Ban...supporting
confidence: 71%
“…The above results verified that the type and content of phenolic compounds in banana peel were varied depending on the variety of banana [11,16]. Similarly, research by Bashmil et al, showed that the highest phenolic compound contents were found in the ripe Ducasse peel, unripe Ladyfinger peel, ripe Plantain peel, and unripe Monkey peel, which contained 1.32, 1.15, 0.87, and 0.79 mg GAE/g, respectively [38]. Baskar et al [39] also found that among the nine local cultivars from Tamil Nadu, India, Poovan cultivar had less total phenolic compound content (0.39 mg catechol equivalent (CE)/g), but higher level of flavonoids (22.83 mg rutin equivalent (RE)/g) in comparison with other cultivars, such as Sevvazhai, Nendran, and Rasthali.…”
Section: Quantitative Analysis Of Main Phenolic Compounds In Ripe Ban...supporting
confidence: 71%
“…As expected, the high-oil-content cultivars had the lowest antioxidant values (Figure S2D,E). In addition, the variations between the results of the DPPH, ABTS, and FRAP assays were attributed to the use of different radicals in the different methods, as the various compounds reacted differently with the employed radicals [42]. Consequently, our findings showed that combining antioxidant capacity assays was more accurate than using only the DPPH assay.…”
Section: Tpc Tfc and Antioxidant Activitiesmentioning
confidence: 77%
“…A previous study reported that the antioxidant activity of oleuropein was mainly due to the aglycones (i.e., hydroxytyrosol moietyin) in its structure [13]. The antioxidant activity of plant-derived samples has shown to be a complicated action that could be synergistically promoted by the various phenolic compounds in the plant [42].…”
Section: Correlation Analysismentioning
confidence: 99%
“…Consequently, the scavenging of • OH radicals by herbal extracts could provide a significant protection to biological damage against these free radicals. Phosphomolybdenum antioxidative power assay (PMAP assay) is used to measure the reduction capacity of molybdenum (VI) to molybdenum (V) by an antioxidant phenolic compound and subsequent formation of a green molybdenum (V)/phosphate complex [ 27 , 28 ]. The results of PMAP assay indicate that rosemary and bay have significantly higher total antioxidant activity (21.93 ± 2.82 and 18.53 ± 0.16 mg AAE/g, respectively) than other listed herbs [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%